STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN MAHASISWA LUAR JAWA - Caetano Gomes Soares Fatima; Herru Prasetya Widodo (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Marketing communications developed in Roman times because at that time people had maintained the awareness that good communications were broadly reaching and prioritizing effectiveness rather than through only individuals. In addition, in Roman times, peopleknew that if people do not know the product, then there would not be an intention or attention to buy. In subsequent developments, marketing communications are not only linked to media usage but include the increased product acquisition and distribution. Therefore, education at the university level is considered very important for the community. The type of research is a qualitative research. Meanwhile the data collection techniques included observation, interviews, documentation, data the analysis technique was by data reduction, data presentation and withdrawal conclusion. The Results of Marketing Communication Strategy used by student admissions section to all students from outside Java were with some marketing communication strategies such as mass media advertisement - poster ads/ banners/education, the website upmb.unitri2017@gmail.com presentation of UPMB program directly to students. The supporting factors in marketing communication strategy of UPMB Unitri in recruiting many students outside Java to study at Unitri Malang. Keywords: Strategy, Improving, Marketing Communication Abstrak: Komunikasi pemasaran berkembang pada masa Romawi karena pada waktu itu masyarakat sudah membertahankan memiliki kesadaran bahwa berkomunikasi yang baik itu adalah jangkauannya luas danmengutamakan efektivitas daripada hanya lewat orang perorangan atau individu. Selain itu, pada masa Romawisudah mengetahui bahwa bila orang tidak tahu akan produk , maka tidak akan ada maksud atau perhatian untuk membeli. Pada perkembangan berikutnya, komunikasi pemasaran bukansaja dihubungkan dalam penggunaan media, melainkan mencakup peningkatan perolehan dan distribusi produk. Oleh sebab itu dengan pendidikan pada tingkat perguruan tinggi dipandang sangat penting bagi masyarakat.Jenis penelitian yang dipilih penelitian kualitatif, teknik pengumpulan data meliputi: observasi, wawancara, dokumentasi, Teknik analisis data dengan cara Reduksi Data, Penyajian Data dan Penarikan Kesimpulan. Hasil Penelitian Strategi Komunikasi Pemasaran: Yang digunakan oleh bagian penerimaan mahasiswa baru pada semua mahasiswa dari luar Jawa dengan beberapa strategi komunikasi pemasaran antara lain: iklan media massa-Iklan poster/ spanduk/ pendidikan, website Upmb.unitri2017@gmail.com presentasi program UPMB langsung kepada siswa-siswa. Faktor pendukung strategi komunikasi pemasaran UPMB Unitri dalam merekrut banyak mahasiswa luar Jawa kuliah di Unitri Malang. Kata Kunci: Strategi, Meningkatkan, Komunikasi Pemasaran